Pengembangan Model Permainan Olahraga Freeball pada Pembelajaran Penjas Adaptif Anak Tunagrahita di SLB Se-Kabupaten Kendal (Journal of Sport Coaching and Physical Education, 2020)
This study aims to develop the Model of Freeball Sports Games in Adaptive Physical Education in SLB in Kendal Regency and to determine the feasibility of Freeball sports game products based on the assessment of adaptive physical experts, modification game experts, and retarded students in SLB. According to Edo Dwi Cahyono in Sugiyono (2011: 297). Research and development methods are methods used to produce certain products, and test the effectiveness of these products. Validation was carried out by adaptive physical material experts, modification game material experts. The developed product was tested for eligibility for mentally retarded students in SLB in Kendal Regency. The results of the study showed that the feasibility level of the Freeball sports game model on adaptive learning for mentally retarded children was assessed: 1) Expert material I at the final stage obtained a value of 87.7% which was included in the "Eligible" category, 2) The final stage II expert material obtained a value of 84.6% which is included in the "Eligible" category, 3) Respondents on a large scale of 20 students, 18 declared worthy of a percentage of 80% while 2 students declared quite decent with the percentage of 20% included in the "Eligible" category of students' responses to this Freeball game model when tested on average showed a positive response by getting a percentage of â‰¥70% for each indicator. Thus the Freeball sports game model in adaptive physical education learning for mentally retarded children in SLB in Kendal Regency is feasible to be used as an adaptive education learning tool in SLB schools.